2004
DOI: 10.1097/00001756-200403010-00034
|View full text |Cite
|
Sign up to set email alerts
|

Non-voluntary and voluntary processing of emotional prosody: an event-related potentials study

Abstract: The present study investigated whether event-related potentials (ERPs) reflect non-voluntary vs voluntary processing of emotional prosody. ERPs were obtained while participants processed emotional information non-voluntarily (i.e. while evaluating semantic characteristics of a stimulus) and voluntarily (i.e. while evaluating emotional characteristics of a stimulus). Results suggest that emotional prosody is processed around 160 ms after stimulus onset under non-voluntary processing conditions (when the attenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
25
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 14 publications
8
25
0
Order By: Relevance
“…Taken together, the above-mentioned findings and related work (de Gelder, Pourtois, & Weiskrantz, 2002;Ishii, Kobayashi, & Kitayama, 2010;Sauter & Eimer, 2010;Wambacq, Shea-Miller & Abubakr 2004) have demonstrated that emotional voices influence listeners by boosting early auditory, and possibly more general (e.g., emotional), processing, regardless of the listeners' concurrent attentional state. However, the extant work is relatively silent on the question of whether emotional voices affect listeners beyond the immediate present.…”
Section: Introductionsupporting
confidence: 53%
See 2 more Smart Citations
“…Taken together, the above-mentioned findings and related work (de Gelder, Pourtois, & Weiskrantz, 2002;Ishii, Kobayashi, & Kitayama, 2010;Sauter & Eimer, 2010;Wambacq, Shea-Miller & Abubakr 2004) have demonstrated that emotional voices influence listeners by boosting early auditory, and possibly more general (e.g., emotional), processing, regardless of the listeners' concurrent attentional state. However, the extant work is relatively silent on the question of whether emotional voices affect listeners beyond the immediate present.…”
Section: Introductionsupporting
confidence: 53%
“…Previous research on vocal encoding had revealed larger P200 amplitudes for emotionally than for neutrally spoken words, highlighting the P200 as a potential marker of emotional processing (Paulmann & Kotz, 2008;Paulmann et al, 2010;Sauter & Eimer, 2010;Wambacq et al, 2004). However, the susceptibility of this component to physical stimulus characteristics raises the possibility that voice-related P200 amplitude differences reflect sensory processing instead.…”
Section: Emotional Encodingmentioning
confidence: 97%
See 1 more Smart Citation
“…In summary, the data diverge considerably on the question of whether the pattern of brain activity is strongly right-lateralized (e.g., Mitchell, Elliott, Barry, Cruttenden, & Woodruff, 2003;Wildgruber et al, 2005) or virtually symmetrical (e.g., Kotz et al, 2003). Among the factors possibly leading to different findings in different imaging studies are task requirements (e.g., paying attention to prosody or not); the amount and importance of semantic information delivered by the same stimuli that bear emotional information (e.g., words, pseudowords, exclamations); specific emotions, such as fear, that lead to particular activation patterns; basic physical stimulus features such as F0, intensity, and (in fMRI experiments) duration; 2 and finally, the nonspecific arousal elicited by stimuli (e.g., Mitchell et al, 2003;Sander et al, 2005;Schirmer et al, 2005;Wambacq et al, 2004;Wildgruber et al, 2005). A recent study even showed that the additional activation of the right middle superior temporal gyrus over its left tempoto disentangle the two components, although both distinguished between emotionally positive standards and emotionally negative deviants.…”
Section: Neurophysiology Of Affective Prosodymentioning
confidence: 99%
“…However, when subjects had to pay attention to prosody and judge its congruence, the difference between men and women disappeared (Schirmer, Kotz, & Friederici, 2005). Wambacq, Shea-Miller, and Abubakr (2004) reported an increased ERP positivity to spoken words with negative affective prosody (as compared with words with neutral prosody), whose latency varied as a function of attention; no interaction between the consecutive words (i.e., priming) was reported. Recently, Kotz and Paulmann (2007) and Paulmann and Kotz (2008b) used a set of sentences containing violations of emotional and semantic context.…”
mentioning
confidence: 96%